Replays of Reports and Songs
06.00-14.00 CET: Replays of report with Egyptian guest, visit to people's houses, finding support for leadership; report on bombed civilian area; report on bombing of a church in Basra; report on downing of American plane; report on bombing near Russian Embassy; report with pictures of "final battle." Songs are interspersed.